Tác động của các đối thủ cạnh tranh trong khu vực phi chính thức đến xuất khẩu của doanh nghiệp tại Việt Nam - Trần Quốc , Trung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This paper examines the impact of competitors in the informal sector on firms’ export performance in Vietnam. The sample includes 1,857 observations from the World Bank’s enterprise survey. Research findings show that competitors in the informal sector have negative impacts on both the likelihood of exporting and export intensity of firms in the formal sector. Consequently, policymakers should effectively manage informal economic activities in order to promote exports. Furthermore, firms should choose an investment destination which has a transparent business environment and a minimal presence of informal sector activities to enhance their export performance.